PENYELESAIAN SENGKETA MEDIS PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 1/PUU-XXIV/2025: ANALISIS KAJIAN PUSTAKA TERHADAP PERUBAHAN PARADIGMA TANGGUNG JAWAB MEDIS DAN DAMPAKNYA TERHADAP HUKUM KESEHATAN INDONESIA - Gunawan Widjaja (JOURNAL OF LAW AND NATION, 2026)
Medical disputes are an increasingly prominent phenomenon within Indonesia’s healthcare system, in line with the public’s growing legal awareness of patients’ rights. This study aims to analyse the shift in the paradigm of medical liability and the impact of Constitutional Court Decision No. 1/PUU-XXIV/2025 on the medical dispute resolution system in Indonesia, using a normative legal research method with a literature review approach. The results of the study indicate that the Constitutional Court’s decision has fundamentally altered the paradigm of medical liability from a fault-based liability approach towards a more proportional system with stronger legal protection for healthcare professionals acting in accordance with professional standards. The mechanism for resolving medical disputes has undergone a transformation with the strengthening of Alternative Dispute Resolution (ADR) as the primary step before litigation, the independence of the Indonesian Health Council (KKI) and the Medical College, and the clarification of the rational boundary between medical risk and criminal negligence through the role of the Professional Disciplinary Council as a professional gatekeeper. The implications for Indonesian health law include the codification of a more effective ADR system, the strengthening of legal protection for healthcare professionals to prevent the criminalisation of medical actions that comply with standards, and the guarantee of access to justice for patients who have genuinely suffered harm through mechanisms that are faster, cheaper, confidential and fair. This study concludes that the transformation of the medical dispute resolution system reflects the maturity of Indonesia’s health law system, which seeks to balance patients’ rights to health and legal protection for healthcare professionals.